The "Triple Depreciation Line" instead of the "Triple Bottom Line": Towards a genuine integrated reporting. (December 2015) - Rambaud, Alexandre; Richard, Jacques
Abstract: The 'Triple Bottom Line' (TBL) is a major and increasingly used socio-environmental accounting framework. However, critical academic examinations of this model have been remained scarce and most importantly, no real alternatives have been developed. Thus this theoretical paper provides a contribution to fill this gap. Through a critical analysis of the TBL, we argue that it suffers from severe limitations. In particular, it does not protect human and natural capital (HNC). As an answer to these problems, we propose and discuss another accounting framework, the 'Triple Depreciation Line' (TDL), which extends to HNC the powerful capitalist accounting tool for preserving financial capital – the historical cost accounting (HCA) and its planned depreciation. To this end, we analyse and (re-)define the concept of capital in an ecological accounting context. We clearly specify the assumptions on which the TDL relies, to facilitate comparisons or dialogues with other accounting models and to avoid misunderstanding as in the case of the TBL. These axioms concern what we call the 'social' (axioms SA1–2) and 'corporate' (axioms AA1–4) capital maintenance. While the two first appeal to the most precise ontological investigation possible of HNC, the others imply mainly the recourse to the HCA and its depreciation.